Dividend Policy as a Moderating Variable on the Effect of SIZE, Debt Policy, and Profitability on Stock Returns - Apriansyah, Poni Melati; Subing, Hesty Juni Tambuati; Sari, Imelda; Nugroho, Randhy (Journal of International Conference Proceedings, 2023)
Currently the economy in Indonesia is developing rapidly. Indonesia's economic growth in 2021 will also improve. The goal of investors investing in a company is to obtain returns. Then, there are several factors that influence stock returns, including company size, debt policy and profitability. This research aims to examine the influence of Company Size, Debt Policy and Profitability on Stock Returns with Dividend Policy as a moderating variable in non-financial companies included in the LQ45 stock index on the Indonesia Stock Exchange (BEI) for the 2017-2022 period. The sample for this company was 18 companies using the purposive sampling method. The analytical method used is multiple linear regression techniques and Moderated Regression Analysis (MRA) testing using the SPSS version 29.0 application. The research results show that company size has a significant effect on stock returns. Debt policy and profitability have no significant effect on stock returns. Dividend policy can moderate company size on stock returns. However, dividend policy does not moderate debt policy and profitability on stock returns.